5G to 6G: A Paradigm Shift in Radio Channel Modeling. Issue 7 (12th July 2022) - Salous, S.; Haneda, K.; Degli‐Esposti, V.
Abstract: Since the publication of the special collection on Radio Channel Modeling for 5G Millimeter Wave Communications in the Built Environments new frequency bands, new antennas and new transmission techniques are being proposed to cope with the demanding requirements of beyond‐5G systems. In this commentary, we provide an overview of the new technology and on how it will impact on radiowave propagation characteristics, and the way radio channel models will be developed and used in the future. Key Points: Radio Channel modeling for 6G Millimeter wave and Terahertz transmission Stochastic and deterministic channel models